PCB (Printed Circuit Board) Etching Machine Using ESP32-Camera Based Internet Of Things - Adi Prasetyo; Jamaaluddin Jamaaluddin; Izza Anshory (Universitas Darul Ulum, 2023)
Today's technology is automated. In car alarm devices, to automatic parking. This very rapid development of technology makes humans create equipment that can make it easier for humans. The etching process can also be called the Printed Circuit Board screen printing process, which is the creation of a path or layout that will connect between electrical components. PCB etching machine is a tool used to dissolve metal parts that are not designed on plain PCB boards using a mixture of chemical solutions, namely ferric chloride. Manual PCB processes usually take a long time and risk being exposed to ferrit chloride solutions for users. This article discusses how to make an automatic etching machine tool with a Microcontroller module that has a camera feature to monitor the editing results on a copper board. With the time method as the key to perfect results during the checking process. For as a driver, that is using a Servo Motor. The microcontroller used in this machine is an ESP32 camera based on the Internet of things Telegram as a Data Base media. For software design using fritzing software applications. The success of the PCB etching machine in this study is seen from testing tools ranging from voltage testing, microcontroller testing, real time a clock testing and Internet of Things system testing. From many of these tests, good results were obtained.